Median Nerve Palsy following Elastic Stable Intramedullary Nailing of a Monteggia Fracture: An Unusual Case and Review of the Literature. (20th April 2011) - Lidder, Surjit; Heidari, Nima; Amerstorfer, Florian; Grechenig, Stephan; Weinberg, Annelie M.
Abstract : Monteggia fractures are rare in children, and subtle radial head dislocations, with minor plastic deformation of the ulna, may be missed in up to a third of cases. Complications of Monteggia fractures-dislocations include persistent radial head dislocation, forearm deformity, elbow stiffness, and nerve palsies at the time of presentation. An unusual case of median nerve palsy following elastic stable intramedullary nailing of a type I Monteggia lesion in a 6-year-old girl is presented, and we highlight that, although most nerve palsies associated with a Monteggia fracture-dislocations are treated expectantly in children, early intervention here probably provided the best outcome.